Comparison of Open vs Endoscopic Surgical Treatment of Haglund’s Deformity - Ahmad, Afaq; Mahmood, Shahid (Indus Journal of Bioscience Research, 2025)
Background: Haglund’s deformity is a common cause of posterior heel pain resulting from a bony enlargement at the posterosuperior aspect of the calcaneus, which can irritate the Achilles tendon and retrocalcaneal bursa. When conservative treatment fails, surgical intervention becomes necessary. Both open and endoscopic surgical techniques are used for its management, but their comparative outcomes remain an area of clinical interest. Objective: To compare the clinical outcomes of open versus endoscopic surgical treatment of Haglund’s deformity in terms of pain relief, functional recovery, postoperative complications, and return to normal activities. Methods: This comparative observational study was conducted at Orthopedic Department Bahawal Victoria Hospital QAMC Bahawalpur from 24 January 2025 to 24 June 2025. A total of 60 patients diagnosed with Haglund’s deformity were included and divided into two groups. Group A (n=30) underwent open surgical treatment, while Group B (n=30) underwent endoscopic surgery. Pain was assessed using the Visual Analog Scale (VAS), and functional outcomes were measured using the American Orthopaedic Foot and Ankle Society (AOFAS) score. Postoperative complications and recovery time were also recorded. Data were analyzed using SPSS version 25, with a p-value ≤0.05 considered statistically significant. Results: Both groups showed significant improvement after surgery; however, the endoscopic surgery group demonstrated lower postoperative pain scores, higher functional outcomes, fewer complications, and a faster return to daily activities compared with the open surgery group. Conclusion: Endoscopic surgical treatment of Haglund’s deformity appears to be a safe and effective alternative to open surgery, offering better postoperative recovery and fewer complications.